The refinement of technology of macaroni products enriched with whortleberry - Holikova, Tatiana; Babich, Oksana (My University, 2016)
The quality of macaroni products with addition of 5 – 10 % whortleberry powder to the weight of flour have got violet color, improved cooking properties. The increasing of whortleberry dosage till 15 % effects more acidity of macaroni and lower durability on 30 %. Whortleberry powder causes decreasing of gluten content and its hydration. And gluten has got more elastic properties. Components of whortleberry effect dehydration of macaroni dough and prevent biopolymers wheat flour to form a dough. Whortleberry powder encourages forming of small friability dough that fasten pressing of products. By means of Box-Wilson method the optimal technological parameters have been determined, such as dosage of whortleberry powder – 4 % to the weight of flour, temperature of water for the dough kneading – 37.
Keywords: macaroni products; whortleberry; quality; enrichment; макаронные изделия; черника; качество; обогащение; макаронні вироби; чорниця; якість; збагачення; кафедра готельно-ресторанної справи